O contrato de transporte aéreo - Sousa, Marco Romão de (2013)
The international conventions and agreements on civil liability emerged with the purpose of regulating the liability of the air carrier, bearing in mind two essential factors: i) the need to protect passengers interests, and ii) to ensure the continuous development of an incipient activity by limiting the compensation amounts. This research will focus on the analysis of the nature of the contract of air carriage, as well as the air carrier's liability regime regarding damages endured by passengers that may result from the non-performance of the contract.